Nedenleri ve Sonuçları ile Çocuk İşçiliği - Ocakçı, Ayşe Ferda; Subaşı, Damla Özçevik; Yüceol, Hüseyin Mualla; Akın, Levent; Dinç Ütükler, İstemi Ceysu and Karadeniz , Meltem and Çatıker, Aslıhan and Tekin Yılmaz, Tülay and Tatoğlu, Nilüfer and Kuzlu Ayyıldız, Tülay and Bozdağ, Fatma and Oruç, Deniz and Ayalp, Mustafa Çağrı and Aygüler, Edip and Ağyar, Esra and Ataman Kufacı, Aynur (Academician Publishing Book DOI Portal, 2024)
-